Positive effects of different drug forms of silybin in the treatment of metabolic syndrome - Poruba, M; Matušková, Z; Kazdová, L; Oliyarnyk, O; Malínská, H; Tozzi di Angelo, I; Večeřa, R (Physiological research, 2015)
Silymarin and silybin are widely used for their hepatoprotective properties. Our previous studies confirm positive effect of silymarin on lipoprotein profile and lipid homeostasis. Advanced drug forms may improve the bioavailability of these compounds. In this study, we investigate the effects of silybin in different drug forms (standardized silybin, micronized silybin, and silybin in form of phytosomes) on dyslipidemia and glucose metabolism in hereditary hypertriglyceridemic (HHTg) rats. Male HHTg rats were divided into four groups of seven animals and were fed by experimental diets. Silybin significantly decreased serum level of triglycerides in groups of rats fed by standardized silybin and silybin in form of phytosomes compared to control group. Results show that silybin did not affect the total cholesterol level, but significantly increased the levels of HDL cholesterol in all groups of animals. Silybin in a standardized form had the highest hypotriglyceridemic effect. On the other hand, the micronized form has caused the highest increase of protective HDL and most significantly decreased glucose and insulin levels. Our results suggest that silybin is probably responsible for some positive properties of silymarin. Subsequent dose-dependent studies of silybin action may reveal the intensity of its positive effects on lipid and glucose parameters.
Keywords: Silybin; Triglycerides; farmaceutická chemie; hypertriglyceridemie; Cholesterol, HDL; potkani transgenní; krysa rodu Rattus; výsledek terapie; zvířata; glukosa; Rats, Transgenic; metabolický syndrom; Hypertriglyceridemia; silibinin; triglyceridy; Male; Insulin; silymarin; Metabolic Syndrome; Glucose; Treatment Outcome; HDL-cholesterol; Rats; Chemistry, Pharmaceutical; Silymarin; Animals; mužské pohlaví; inzulin